Dermoid cyst and uveitis: coexistence or coincidence? - Klemenska, Paula; Pierudzka, Weronika; Kuchalska, Katarzyna; Gotz-Więckowska, Anna; Chmielarz-Czarnocińska, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2025)
The study describes the case of a 4-year-old girl who presented to the ophthalmology emergency department with redness and pain in her right eye. During the physical examination of the anterior segment of the right eye, mixed injection, posterior synechiae of the iris, and inflammatory cells in the anterior chamber were observed. Based on the suspicion of anterior uveitis, treatment was initiated. Due to difficulty visualizing the fundus of the right eye during diagnostic work-up, an orbital ultrasound was performed, revealing a tumor located behind the globe. Radiological findings suggested features of malignancy. However, histopathological examination confirmed that the lesion was a dermoid cyst in a less common location. Further diagnostic evaluations for uveitis raised suspicions of juvenile idiopathic arthritis (JIA). It was concluded that uveitis and the dermoid cyst were distinct, unrelated conditions diagnosed in this patient. To the authors’ knowledge, no similar case involving the coincidence of these two conditions has been reported in the existing literature.